Common Features of the Metabolic Syndrome and Nonalcoholic Fatty Liver Disease - Almeda-Valdes, Paloma; Aguilar-Olivos, Nancy; Uribe, Misael; Mendez-Sanchez, Nahum (Reviews on Recent Clinical Trials, 2014)
Nonalcoholic fatty liver disease (NAFLD) is an important cause of chronic liver disease; including simple steatosis, steatohepatitis, fibrosis, or cirrhosis. The metabolic syndrome (MS) is the existence of metabolic alterations that confer an increased risk for developing cardiovascular disease and diabetes. NAFLD and MS frequently coexist and 90% of NAFLD patients have more than one manifestation of the MS. In addition, both entities are related to other comorbid conditions. Scientific advances in the understanding of the association between NAFLD and the MS have identified insulin resistance as a key aspect in the pathophysiology of both diseases. Knowledge gained from these advances can be applied clinically in the management and prevention of NAFLD, the MS, and associated metabolic alterations. Cardiovascular disease is the leading cause of death in patients with NAFLD and the MS, therefore adequate diagnosis and effective treatment are critical. This review analyzes current evidence of the association between NAFLD and the MS. The growing prevalence of both entities is highlighted. Next, the common mechanisms leading to insulin resistance are discussed. Manifestations and diagnosis of the MS and NAFLD are reviewed, pointing out the associated comorbid conditions shared by both diseases. Finally, a brief overview regarding NAFLD treatment is presented.
Keywords: nonalcoholic steatohepatitis